Peningkatan Hasil Belajar Penjumlahan dan Pengurangan Bilangan Siswa Kelas I dengan Media Konkret - Pujasmara, Destiani Dwi; Humaira, Jihan; Alifah, Putri Zahra; Mariana, Yulia Alda; Rostika, Rd. Deti (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Mathematics learning is still a problem for many students. This can be seen from the average mathematics scores being lower than other subjects. Of the 23 first grade students at SDN Haurpugur 02 Elementary School, only 8 students or 34.78% have completed mathematics learning, while 15 students or 65.21% have not, especially on addition and subtraction materials. To teach this material, a suitable learning medium is concrete objects so that students get real and concrete learning experiences according to their developmental stage. This classroom action research was conducted by applying concrete object media in learning mathematics on addition and subtraction materials. The results showed an increase in student activity and learning outcomes. In Cycle I using concrete object media, 20 students (62.5%) have completed. In Cycle II the number of students completed increased to 28 students (90.63%). Thus it can be concluded that the use of concrete object media can improve student learning outcomes in addition and subtraction materials.